Al-Takāmul al-Tarbawī bayna al-Maʿhad wa al-Usrah fī Tanmiyat Mahārat al-Kalām ladā Mutaʿallimī al-ʿArabiyyah: Dirāsat Ḥālah fī Ta’limi al- Ma’had Al-Jaami’ah - Saiul Anah; Sayyidah (Al-Fakkaar, 2026)
This study analyzes the role of pedagogical integration between an Islamic boarding school and parents in developing students’ Arabic speaking skills fi Ta’limi al-Ma’had al-Jaami’ah. The research aims to identify forms of educational collaboration and their contribution to sustaining students’ language practice. This qualitative case study involved language center supervisors, teachers, parents, and students. Data were collected through interviews, observations, and document analysis, and analyzed using the Miles and Huberman model. The findings show that integration through periodic reports, direct meetings, motivational support, and home language activities strengthens students’ confidence, language discipline, and speaking practice. The study concludes that collaboration between the institution and families creates an extended language environment that supports the development of communicative competence and sustainable speaking skills.